2017
DOI: 10.3346/jkms.2017.32.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Solifenacin 5 mg Fixed Dose in Korean Children with Newly Diagnosed Idiopathic Overactive Bladder: a Multicenter Prospective Study

Abstract: We investigated the efficacy and tolerability of solifenacin 5 mg fixed dose in children with newly diagnosed idiopathic overactive bladder (OAB). A total of 34 children (male/female patients = 16/18) aged under 13 years (mean age: 7.2 ± 2.3; range: 5–12) who were newly diagnosed with OAB from January 2012 to September 2014 were prospectively evaluated with open-label protocol. All patients were treated with solifenacin 5 mg fixed dose once daily for at least 4 weeks. The efficacy and tolerability of solifenac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Inclusion criteria were men of ≥40 years of age showing poor efficacy in OAB symptoms improvement after at least 4 weeks of low-dose antimuscarinic treatment (propiverine, 10 mg or tolterodine, 2 mg) [ 12 ]. Due to this, treatment was changed to standard dose antimuscarinic treatment [ 13 ] using solifenacin (5 mg) for more than 12 weeks. ‘Poor efficacy’ was defined as a total overactive bladder symptom score (OABSS) of ≥3, and/or ≥2 points in the OABSS questionnaire number 2 with the reference to the definition of OAB [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were men of ≥40 years of age showing poor efficacy in OAB symptoms improvement after at least 4 weeks of low-dose antimuscarinic treatment (propiverine, 10 mg or tolterodine, 2 mg) [ 12 ]. Due to this, treatment was changed to standard dose antimuscarinic treatment [ 13 ] using solifenacin (5 mg) for more than 12 weeks. ‘Poor efficacy’ was defined as a total overactive bladder symptom score (OABSS) of ≥3, and/or ≥2 points in the OABSS questionnaire number 2 with the reference to the definition of OAB [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…8 Solifenacin succinate is a competitive antimuscarinic with better M3 selectivity postulated to reduce side effects compared to oxybutynin, trospium chloride, and tolterodine, approved worldwide at daily doses of 5 and 10 mg for the treatment of urinary frequency, UI, or adult OAB, and has showed good tolerability and efficacy in adult clinical studies. 7,8 Meanwhile, solifenacin wasn't approved by the FDA to be used in children, 9 many studies were done suggesting safety and efficacy of solifenacin in pediatric OAB. [8][9][10] Until now, there is a limited knowledge on the usage of solifenacin in the treatment of nocturnal enuresis and the optimal dose wasn't determined.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Meanwhile, solifenacin wasn't approved by the FDA to be used in children, 9 many studies were done suggesting safety and efficacy of solifenacin in pediatric OAB. [8][9][10] Until now, there is a limited knowledge on the usage of solifenacin in the treatment of nocturnal enuresis and the optimal dose wasn't determined.…”
Section: Introductionmentioning
confidence: 99%
“…Solifenacin treatment led to statistically significant improvements in mean voiding frequency and mean volume voided (MVV) following administration to 34 children with newly diagnosed OAB and 138 children with therapy-resistant OAB, respectively. 24,25 In addition, the results of phase III trials in children and adolescents with OAB showed that oral solifenacin suspension was superior to placebo in terms of MVV and was well tolerated over 52 weeks of treatment, with the majority of adverse events being mild or moderate in severity and no treatment-related serious adverse events being reported. 26,27 No unexpected safety concerns were apparent when solifenacin suspension was administered to children and adolescents with NDO and the drug appeared to be an efficacious and well-tolerated treatment, with a minority of patients reporting adverse events, when it was used to treat children with oxybutynin-or tolterodine-refractory NDO.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have also been conducted with a solifenacin suspension that has been formulated for use in pediatric patients. Solifenacin treatment led to statistically significant improvements in mean voiding frequency and mean volume voided (MVV) following administration to 34 children with newly diagnosed OAB and 138 children with therapy‐resistant OAB, respectively 24,25 . In addition, the results of phase III trials in children and adolescents with OAB showed that oral solifenacin suspension was superior to placebo in terms of MVV and was well tolerated over 52 weeks of treatment, with the majority of adverse events being mild or moderate in severity and no treatment‐related serious adverse events being reported 26,27 .…”
Section: Introductionmentioning
confidence: 99%